Postural control of arm and fingers through integration of movement commands - Scott T Albert; Alkis M Hadjiosif; Jihoon Jang; Andrew J Zimnik; Demetris S Soteropoulos; Stuart N Baker; Mark M Churchland; John W Krakauer; Reza Shadmehr (eLife, 2020)
Every movement ends in a period of stillness. Current models assume that commands that hold the limb at a target location do not depend on the commands that moved the limb to that location. Here, we report a surprising relationship between movement and posture in primates: on a within-trial basis, the commands that hold the arm and finger at a target location depend on the mathematical integration of the commands that moved the limb to that location. Following damage to the corticospinal tract, both the move and hold period commands become more variable. However, the hold period commands retain their dependence on the integral of the move period commands. Thus, our data suggest that the postural controller possesses a feedforward module that uses move commands to calculate a component of hold commands. This computation may arise within an unknown subcortical system that integrates cortical commands to stabilize limb posture.